Comparative estimation of maternal and fetal thrombophilia in patients with early (under 34 weeks of gestation) and late forms of pre-eclampsia - M. D. Andreeva (Кубанский научный медицинский вестник)
The article presents the results of the comparative analysis of maternal and fetal thrombophilia in patients with early (under 34 weeks of gestation) and late forms of pre-eclampsia. The diagnosing of latent acquired and genetic thrombophilia in women of high risk groups makes possible to predict the risk of pre-eclampsia and to substantiate the prophylaxis of complicated pregnancy. Such prophylaxis reduces the rate and the heaviness of pre-eclampsia and the number of perinatal complications.